Geographic distribution of health services in the breast cancer care pathways in Pernambuco, Northeast of Brazil - Rosalva Raimundo da Silva; Iris Edná Pereira da Silva; Geyssyka Morganna Soares Guilhermino; Wisley Donizetti Velasco; Isabel Cristina Areia Lopes Pereira; Tereza Maciel Lyra (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to analyze the geographic distribution of breast cancer care services in Pernambuco, northeastern Brazil. Methods: a descriptive cross-sectional study analyzing the geographic distribution of breast cancer care services, which used the National Registry of Health Facilities, State Oncology Plan, and Outpatient and Hospital Information Systems, in 2022. The tools used in the analysis were Excel 2021, TabWinDataSUS, and Geo-clip Dubbed version. Results: the geographic distribution and care flows revealed regional disparities, especially in macro-regions II, III, and IV. Macro-region I is the best equipped, concentrating the majority of mammograms (64.4%), in addition to having the majority of ultrasound equipment (64.5%) and cancer treatment services (65.1%). The absence of breast biopsy services in the SUS was observed in the National Registry of Health Facilities. Of the seven units indicated in the oncology plan, three did not perform biopsies in the last five years, and two started in 2022. Conclusion: the results highlighted the need for (re) organization of the breast cancer care network and the distribution of health services, considering local needs, through the implementation of the care line with adequate flows, providing timely and equitable care.